The Deferred African American Dream Depicted in Harlem by Langston Hughes and Lorraine Hansberry's a Raisin in the Sun - Syaila Nur Amaliyah (Jurnal Indonesia Sosial Sains, 2024)
This research analyzes how the American Dream is represented and why the depiction of the dream is written as a dream "deferred" in Langston Hughes's poem Harlem and Lorraine Hansberry's play A Raisin in the Sun. Systemic racism and economic limitations have historically prevented many African Americans from achieving the American Dream, their dream in this case being equal opportunity and financial stability. This research uses qualitative methods, based on the Sociology of Literature theory of Rene Wellek and Austin Warren, to analyze how Hughes and Hansberry depict the American dream and the effects of African Americans' challenges in pursuing their aspirations in the 1950s. The result of this study shows that The American Dream for the Younger family includes a decent home, a fulfilling job, and educational opportunities. Mama's desire for a better home reflects the aspirations of African Americans. Despite obstacles, Mama remains resilient, supporting Walter's business ambitions and Beneatha's dream of becoming a doctor. Economic limitations and racial discrimination pose challenges, impacting the family's well-being. Yet, their unity and determination symbolize resilience. Hughes' "Harlem" highlights the consequences of deferred dreams, mirroring the family's struggles. These narratives underscore the importance of perseverance and unity in pursuing the American Dream amidst adversity.